2017
DOI: 10.1038/labinvest.2017.65
|View full text |Cite
|
Sign up to set email alerts
|

Paired related homeobox protein 1 regulates PDGF-induced chemotaxis of hepatic stellate cells in liver fibrosis

Abstract: Activation of the platelet-derived growth factor (PDGF)/PDGF beta receptor (PDGFβR) axis has a critical role in liver fibrosis. However, the mechanisms that regulate the PDGF signaling are yet to be elucidated. The present study demonstrates that paired related homeobox protein 1 (Prrx1) is involved in PDGF-dependent hepatic stellate cell (HSCs) migration via modulation of the expression of metalloproteinases MMP2 and MMP9. PDGF elevated the level of Prrx1 through the activation of ERK/Sp1 and PI3K/Akt/Ets1 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…One of few established target genes of PRRX1 is tenascin C (TNC) 35,36 , a pro-fibrotic factor involved in a Twist1-Prrx1-TNC positive feedback loop in fibroblast activation 37 . Recent studies have revealed pro-fibrotic effects of PRRX1 in hepatic stellate cells 38 and lung fibroblasts 39 . In hepatic stellate cells, PRRX1 was shown to transactivate the COL1A1 promoter 40 .…”
Section: Discussionmentioning
confidence: 99%
“…One of few established target genes of PRRX1 is tenascin C (TNC) 35,36 , a pro-fibrotic factor involved in a Twist1-Prrx1-TNC positive feedback loop in fibroblast activation 37 . Recent studies have revealed pro-fibrotic effects of PRRX1 in hepatic stellate cells 38 and lung fibroblasts 39 . In hepatic stellate cells, PRRX1 was shown to transactivate the COL1A1 promoter 40 .…”
Section: Discussionmentioning
confidence: 99%
“…ETS1 is a known transducer of growth factor and ERK signaling controlling genes involved in inflammation, proliferation, and ECM remodeling 24,5255 and has previously been detected in HSCs 55,56 . ETS1 is permissive of TGFβ signaling to Smad2/3-regulated genes in HaCaT keratinocytes, where 56% of Smad2/3-binding regions also contain ETS1 motifs 57 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that ERK1/2 activation increases the expression of MMP9, a metalloprotease involved in degradation of the extracellular matrix (Duarte et al, 2015; Hamada et al, 2008) whose promoter contains AP1 binding domains (Loesch et al, 2010). Several studies have reported elevations of this metalloprotease during the fibrotic process in livers from both humans and rodents (Arthur, 2000), suggesting a pivotal role of ERK1/2 in its induction in HSCs (Gong et al, 2017; Loesch et al, 2010). Analysis of MMP9 expression revealed a significant increase in LX2 cells treated with IGF1; an effect that was abolished by the presence of PD98059 or in IRS2 -silenced cells in which ERK1/2 phosphorylation was decreased.…”
Section: Discussionmentioning
confidence: 99%